2021
DOI: 10.3892/ol.2021.12848
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 is a prognostic marker that inhibits the invasion and migration of gastric cancer by regulating VEGF expression

Abstract: Metastasis is the main cause of poor prognosis of patients with gastric cancer (GC). Thus, current research is focused on identifying biomarkers that can predict the prognosis of patients with GC. C-X-C motif chemokine receptor 4 (CXCR4) and vascular endothelial growth factor (VEGF) have been reported to play important roles in different types of malignancies; however, their role in the prognosis of GC remains unknown. The present study aimed to investigate the potential role of CXCR4 and VEGF in predicting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Previous studies have shown that gastric cancer patients with high expression of CXCR4 have a poor prognosis and therefore, CXCR4 can be used as a prognostic marker of gastric cancer [36,37]. CXCR4 is a stem cell marker of GC cells and promote their proliferation and metastasis [36][37][38][39][40][41]. Further studies showed that the knockdown or addition of the KDM6B enzyme activity inhibitor, GSK-J4, can downregulate the expression of CXCR4 in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that gastric cancer patients with high expression of CXCR4 have a poor prognosis and therefore, CXCR4 can be used as a prognostic marker of gastric cancer [36,37]. CXCR4 is a stem cell marker of GC cells and promote their proliferation and metastasis [36][37][38][39][40][41]. Further studies showed that the knockdown or addition of the KDM6B enzyme activity inhibitor, GSK-J4, can downregulate the expression of CXCR4 in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we selected CXCR4 as a downstream target gene of KDM6B. Previous studies have shown that gastric cancer patients with high expression of CXCR4 have a poor prognosis and therefore, CXCR4 can be used as a prognostic marker of gastric cancer [36,37]. CXCR4 is a stem cell marker of GC cells and promote their proliferation and metastasis [36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we selected CXCR4 as a downstream target gene of KDM6B. Previous studies have shown that gastric cancer patients with high expression of CXCR4 have a poor prognosis and therefore, CXCR4 can be used as a prognostic marker of gastric cancer 36,37 . CXCR4 is a stem cell marker of GC cells and promote their proliferation and metastasis [36][37][38][39][40][41] .…”
Section: Helicobacter Pylori Infection Promotes the Expression Of Kdm6bmentioning
confidence: 99%
“…Previous studies have shown that gastric cancer patients with high expression of CXCR4 have a poor prognosis and therefore, CXCR4 can be used as a prognostic marker of gastric cancer 36,37 . CXCR4 is a stem cell marker of GC cells and promote their proliferation and metastasis [36][37][38][39][40][41] . Further studies showed that the knockdown or addition of the KDM6B enzyme activity inhibitor, GSK-J4, can downregulate the expression of CXCR4 in gastric cancer cells.…”
Section: Helicobacter Pylori Infection Promotes the Expression Of Kdm6bmentioning
confidence: 99%
“…Além disso, o eixo CXCR4/CXCL12 regula positivamente a expressão de VEGF. A inibição de CXCR4 inibe a formação de novos vasos em camundongos imunodeficientes e reduz a migração e invasão in vitro de células oriundas de pacientes com câncer gástrico (Salvucci et al 2002;Chen et al 2021).…”
Section: Cits E Metástaseunclassified